Social-environmental Determinants of Graduates Innovativeness Development in Selected East Africa Countries - (:unkn) unknown (My University, 2022)
Joint effort is required in promoting innovation beyond classroom in the face of fostering human development globally. This study assessed social environmental determinants for graduates’ innovativeness development in selected East Africa countries. Cross-sectional research design was employed where data were collected once. The data were descriptively analyzed through mean ranking and percents. The results generally show that university and related higher learning institutions were found as the key innovation support determinant for the graduates followed by suppliers of the equipment in the region. It was further found that the graduates who developed innovation rarely protect their innovations. This led graduates not to benefit from their intellectual property copy rights and associated recognized innovation benefits. It is concluded that the number of social environmental determinants that support graduates innovation persist in east African countries, however, majority of graduates do not utilize such opportunities for innovation development. It is recommended that the capacity building and stakeholders engagement measures need to be immediately conducted.
Keywords: African Research